Réponses

2014-05-21T14:50:22+02:00
A = 4(x + 5) = 10x + 3
4x + 20 = 10x + 3
4x - 10x = 3 - 20
- 6x = - 17
x = 17/6

B = 3 (x - 2) = 6 (x + 4).
3x - 6 = 6x + 24
3x - 6x = 24 + 6
- 3x = 30
x = - 30/3
x = - 10

C = 7x - (5x + 3) = 5 (x - 3) + 2
7x - 5x - 3 = 5x - 15 + 2
7x - 5x - 5x = - 15 + 2 + 3
- 3x = - 10
x = 10/3

D = 7 (n + 2) - 3 = 25 - (3n + 4)

7n + 14 - 3 = 25 - 3n - 4
7n + 3n = 25 - 4 - 14 + 3
10n = 10
n = 10/10
n = 1
2014-05-21T14:56:54+02:00
A=4(x+5)= 10x +3
4x +20= 10x +3
4x +20 -20 -10x= 10x +3 -20 -10x
-6x= -17
-6x/ -6= -17/ -6
x= 17/6

B= 3(x-2)=6(x+4)
3x -6= 6x +24
3x -6 +6 -6x= 6x +24 +6 -6x
-3x= 30
-3x/-3= 30/-3
x= -10

C= 7x-(5x +3)= 5(x-3) +2
7x -5x -3= 5x -15 +2
7x -5x -3 +3 -5x= 5x -15 +2 +3 -5x
-3x= -10
-3x/-3= -10/-3
x= 10/3

D= 7(n+2) -3= 25-(3n +4)